The Story of the Companions of the Cave and Modern Temporal Disruption: A Conceptual Analysis of the Quran in the Context of Artificial Intelligence - Salsabila Najma Chaniago; Anita Salsabila; Fathima Sharaniya (Yayasan Albahriah Jamiah Indonesia, 2026)
The acceleration of computation, simultaneous processing, and predictive logic in artificial intelligence has disrupted the way humans understand time, which was previously perceived as linear, sequential, and progressive. Meanwhile, studies of the story of the Companions of the Cave in the Quran are still predominantly placed within a historical-didactic framework, so that its conceptual potential in reading the problems of modern temporality has not been adequately explored. This study aims to explicitly and purposefully analyze the construction of nonlinear temporality in the story of the Companions of the Cave and to engage in critical dialogue with the algorithmic temporality that underlies AI work. This study uses a qualitative approach based on conceptual-thematic analysis of Quranic verses related to time, with a method of critical-comparative dialogue between classical and contemporary interpretations, and theories of temporality in artificial intelligence studies. The results show that the story of the Companions of the Cave represents a nonlinear temporality model that emphasizes the relativity of human time experience, where objective duration is not identical to subjective perception. The conceptual analysis reveals three distinct temporal regimes: human temporality, existential, limited, and experienced; the quantitative, computational, and predictive temporality of machines; and the transcendent, absolute, and beyond-calculation divine temporality. This comparison emphasizes the ontological limits that AI cannot overcome, despite its massive, simultaneous time-processing capacity. In conclusion, the story of the Companions of the Cave expands the horizon of Quranic thematic interpretations of time. It provides a critical framework for assessing claims of artificial intelligence’s temporal supremacy in the modern context.